First Analysis of the Rehabilitation and Release Facilities for Javan Hawk-eagle (Nisaetus bartelsi Stresemann, 1924) in Indonesia - Munawir, Ahmad; Mardiastuti, Ani; Masy’ud, Burhanuddin; Prawiradilaga, Dewi Malia (Media Konservasi, 2025)
The Javan hawk-eagle (Nisaetus bartelsi Stresemann, 1924), an endangered bird endemic to Java island, faces significant extinction risks due to habitat loss and illegal hunting. To address this, the Javan Hawk-eagle Sanctuary Center (JHESC) was established within Mount Halimun Salak National Park, Bogor Regency, West Java, Indonesia, to support in-situ and ex-situ conservation efforts, focusing on rehabilitation and release. This study observed rehabilitation practices at the centre from April 2022 to March 2023, particularly the adequacy of its facilities and infrastructure regarding cage, feed, and health management. These aspects are essential for rehabilitation success. Based on observations, nine cage types were employed and tailored to specific rehabilitation stages: acceptance, treatment, isolation, pre-training, training, habituation, education, translocation, and hard release. These cages were designed with varying sizes and numbers to fulfil the needs of each stage. The centre's feeding management was supported by a well-organized storage system that maintained feed quality through proper air circulation and cleanliness. The centre consistently supplied three primary feeds: mice (Mus musculus), rats (Rattus norvegicus), and marmots (Cavia porcellus). Comprehensive infrastructure facilitated health management, including an animal clinic, isolation and treatment rooms, an operating room, an examination room, and a laboratory. Additionally, the veterinary medicines were accessible and staffed by qualified veterinarians to ensure the eagles were healthy from arrival to release. These robust facilities and practices can position the centre as a leading example for ex-situ conservation, prioritizing animal welfare while rehabilitating and releasing Javan hawk-eagles, with expectations of further enhancing eagle conservation efforts.